The complete mitochondrial genome of Monochamus dubius Gahan (Coleoptera: Cerambycidae) - Wu, Jiankai (Mitochondrial DNA B Resour, 2021)
In this study, we sequenced the complete mitochondrial genome of Monochamus dubius Gahan 1894. The results showed that the length of complete mitochondrial genome was 16,029 bp with 22.22% GC content, containing 39.4% A, 38.4% T, 13.4% C, 8.8% G. There were 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNA), two ribosomal RNA genes (rRNA) and one AT-rich region. Phylogenetic analysis showed that M. dubius was clustered with Monochamus urussovii and Monochamus alternatus alternatus, and confirmed the sister relationship among the genus Monochamus, Anoplophora, and Aristobia from Cerambycidae. The complete mitogenome of M. dubius would help understand the classification and phylogeny of Chrysomeloidea.